Enantio- and regioselective iridium-catalyzed allylic esterification - Qu, Jianping; Roßberg, Lydia; Helmchen, Günter (Journal of the American Chemical Society, 2014)
A highly enantioselective and regioselective Ir-catalyzed allylic esterification is described, in which branched allylic esters are synthesized directly. Carboxylates were used as nucleophiles and linear allylic phosphates as electrophiles. In some cases the allylic substitution reaction was found to be accompanied by a kinetic resolution process, which causes a change of the enantiomeric excess.
Gesehen am 12.10.2020